THE RELATIONSHIP OF LEADERSHIP STYLE AND ORGANIZATIONAL CULTURE: TO EMPLOYEES PEROMANCE OF BANK PAPUA JAKARTA - Amogoso, Jemis; Sihombing, Christina Natalia (Universitas Kristen Indonesia, 2018)
The influence of style leadership and organizational culture for employee performance in each company, the purpose of this research is to test the relationship between style leadership and organizational culture, employee performance in PT. Bank Papua brand DKI Jakarta. This study examines the influence of style leadership and organizational culture, employee performance. Samples of 30 employees. The results of this study indicate that style leadership significantly affects performance. Furthermore, organizational culture has a significant effect on performance.Keywords: Style Leadership and Organizational culture, Employees Performance